AKTIVITAS PENGHAMBAT LIPASE AKTIVITAS PENGHAMBAT LIPASE PANKREAS In Vitro dan STANDARISASI EKSTRAK BANGLE (Zingiber cassumunar ROXB.) - Aryantini, Dyah (Acta Pharmaceutica Indonesia, 2024)
A body mass index of ≥30 kg/m2 indicates obesity, which is brought on by an excess of fat deposits. blocking obesity can be achieved in part by blocking the pancreatic enzyme lipase from doing its job. A plant belonging to the Zingiberaceae family, bangle rhizome has been used traditionally for body slimming and stomach reduction. Standardization is required to guarantee the quality of Bangle extract as a basic material for traditional medicine. The study aim were evaluate specific and non-specific character to standardize Bangle extract and to conduct the inhibitory activity of lipase enzyme activity in vitro. Maceration is used to create the extract, and the extract is subsequently examined for loss of drying, microscopic, phytochemical screening and ethanol and water-soluble extract content. In vitro tests were carried out using the colorimetric method to determine the percentage of inhibition of bangle extract against lipase. The ideal lipase incubation conditions were maintained at 37 OC, pH 7, for 10 minutes. The water content and total ash content yield respectively of 9.42% ± 0.36 and 0,7%±0,02 while the water and ethanol soluble extract levels were 16.96 and 15.13%, respectively. When tested against the pancreatic lipase enzyme at a concentration of 100 ppm, the bangle extract shown a 27.21%±1.59 inhibition of the enzyme. Bangle extract exhibits strong activity in suppressing the pancreatic lipase enzyme in vitro, and overall, both specific and non-specific parfameters of the extract have met the standard requirements.